Nutritional, phytochemical and pharmacological properties of Canarium odontophyllum Miq. (dabai) fruit - Tan, Chin Xuan; Azlan, Azrina (Universiti Putra Malaysia Press, 2016)
Canarium odontophyllum Miq. fruit, popularly recognized as dabai fruit in Sarawak, is a seasonal fruit found in the tropical rainforest of East Malaysia. A dabai fruit can be divided into several anatomical parts, and different parts of the fruit have different valuable phytochemicals. Due to the lack of promotion, dabai fruit is viewed as nutritionally inferior fruit by the public. On the contrary, the fruit is rich in nutrients such as protein, fat, carbohydrates, sodium, calcium and iron. Many phytochemicals have been detected from different parts of dabai fruit, and these molecules have been linked to beneficial properties such as hypolipidemic, anti-atherosclerotic, anti-cholinesterase, antimicrobial and potentially anti-diabetic. The aim of this article is to review research studies on this fruit in order to provide adequate baseline information for commercial exploitation as well as for future studies.